How to make a living from music : a training tool - Stopps, David (World Intellectual Property Organization, 2022)
Building a successful career in music involves abilities to manage intellectual property (IP) rights. WIPO supports authors and performers in enhancing their knowledge of the intellectual property aspects involved in their professional work. Copyright and related rights can help musical authors and performers to generate additional income from their talent